Physio-Biochemical, Anatomical, and Molecular Analysis of Resistant and Susceptible Wheat Cultivars Infected with TTKSK, TTKST, and TTTSK Novel Puccinia graminis Races - Hayat Ali Alafari; Yaser Hafez; Reda Omara; Rasha Murad; Khaled Abdelaal; Kotb Attia; Amr Khedr (Plants, 2024)
Stem rust, caused by Puccinia graminis f.sp. tritici, is one of the most dangerous rust diseases on wheat. Through physiological, biochemical, and molecular analysis, the relationship between the change in resistance of 15 wheat cultivars to stem rust disease and the response of 41 stem rust resistance genes (Sr,s) as well as TTKSK, TTKST, and TTTSK races was explained. Some cultivars and Sr genes, such as Gemmeiza-9, Gemmeiza-11, Sids-13, Sakha-94, Misr-1, Misr-2, Sr31, and Sr38, became susceptible to infection. Other new cultivars include Mir-3 and Sakha-95, and Sr genes 13, 37, 40, GT, and FR*2/SRTT3-SRTT3-SR10 remain resistant. Some resistance genes have been identified in these resistant cultivars: Sr2, Sr13, Sr24, Sr36, and Sr40. Sr31 was not detected in any cultivars. Reactive oxygen species such as hydrogen peroxide and superoxide, enzymes activities (catalase, peroxidase, and polyphenoloxidase), and electrolyte leakage were increased in the highly susceptible cultivars, while they decreased in the resistant ones. Anatomical characteristics such as the thickness of the epidermis, ground tissue, phloem tissue and vascular bundle diameter in the midrib were decreased in susceptible cultivars compared with resistant cultivars. Our results indicated that some races (TTKSK, TTKST, and TTTSK) appeared for the first time in Egypt and many other countries, which broke the resistant cultivars. The wheat rust breeding program must rely on land races and pyramiding genes in order to develop new resistance genes that will survive for a very long time.